2022
DOI: 10.1038/s41581-022-00589-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of the cGAS–STING pathway in systemic and organ-specific diseases

Abstract: Cells are equipped with numerous sensors that recognize nucleic acids, which probably evolved for defence against viruses. Once triggered, these sensors stimulate the production of type I interferons and other cytokines that activate immune cells and promote an antiviral state. The evolutionary conserved enzyme cyclic GMP–AMP synthase (cGAS) is one of the most recently identified DNA sensors. Upon ligand engagement, cGAS dimerizes and synthesizes the dinucleotide second messenger 2′,3′-cyclic GMP–AMP (cGAMP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(63 citation statements)
references
References 193 publications
2
61
0
Order By: Relevance
“…cGAS activation also causes other diseases, including neurological and macular degeneration and liver and renal diseases. Several excellent reviews discussed these topics [ 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ]. Therefore, we discussed these diseases briefly in the following section…”
Section: Cgas-sting Pathway and Pathologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…cGAS activation also causes other diseases, including neurological and macular degeneration and liver and renal diseases. Several excellent reviews discussed these topics [ 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ]. Therefore, we discussed these diseases briefly in the following section…”
Section: Cgas-sting Pathway and Pathologiesmentioning
confidence: 99%
“…Moreover, aging is a crucial factor in precipitating neurological disorders via augmenting cGAS-STING signaling and generation of aged diploid fibroblast cells [ 172 , 179 , 180 , 181 ]. In Alzheimer’s patients, oxidative stress induced by the accumulation of tau and beta-amyloid protein aggregates in the neurons leads to cell death and activation of cGAS-STING signaling [ 178 , 180 , 182 , 183 ].…”
Section: Cgas-sting Pathway and Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…cGAMP binds to the stimulator of interferon genes (STING) localized at the endoplasmic reticulum (ER) membrane ( 10 ). Upon activation, STING, an important signaling component of the DNA sensing pathway that induces type-I IFN production, recruits TANK-binding kinase-1 (TBK1) to form a STING-TBK1 complex ( 9 , 11 ). The STING-TBK1 complex then translocates from the ER to the perinuclear lysosomal compartment through an autophagy-like process and subsequently activates the transcription factors IRF3 and NF- κB ( 9 , 10 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cGAS, a major DNA sensor, produces the second messenger 2',3'-cyclic GMP-AMP to activate STING, leading to the production of type I interferons and other immune mediators. (6) In addition to bacterial and viral DNAs, host self-genomic or mitochondrial DNA can stimulate cGAS (31). Recent studies have shown that the cGAS-STING pathway plays an important role in various liver diseases.…”
mentioning
confidence: 99%